Development and Bioactivity of Zinc Sulfate Cross-Linked Polysaccharide Delivery System of Dexamethasone Phosphate - Natallia V. Dubashynskaya; Anton N. Bokatyi; Andrey S. Trulioff; Artem A. Rubinstein; Igor V. Kudryavtsev; Yury A. Skorik (MDPI AG, 2023)
Improving the biopharmaceutical properties of glucocorticoids (increasing local bioavailability and reducing systemic toxicity) is an important challenge. The aim of this study was to develop a dexamethasone phosphate (DexP) delivery system based on hyaluronic acid (HA) and a water-soluble cationic chitosan derivative, diethylaminoethyl chitosan (DEAECS). The DexP delivery system was a polyelectrolyte complex (PEC) resulting from interpolymer interactions between the HA polyanion and the DEAECS polycation with simultaneous incorporation of zinc ions as a cross-linking agent into the complex. The developed PECs had a hydrodynamic diameter of 244 nm and a ζ-potential of +24.4 mV; the encapsulation efficiency and DexP content were 75.6% and 45.4 μg/mg, respectively. The designed DexP delivery systems were characterized by both excellent mucoadhesion and prolonged drug release (approximately 70% of DexP was released within 10 h). In vitro experiments showed that encapsulation of DexP in polysaccharide nanocarriers did not reduce its anti-inflammatory activity compared to free DexP.